EVALUASI PERFORMA TOUR GUIDE BERBAHASA INGGRIS HIMPUNAN PRAMUWISATA INDONESIA DI TAMAN WISATA CANDI PRAMBANAN - , ERWIN DWISASONGKO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia has abundant tourism potential, one of its kind is cultural tourism which be related to heritage in particular such as temple. The most famous one is Prambanan temple. Prambanan is an area that has been recognized by UNESCO as a world heritage and is managed by PT. Taman Wisata Candi Prambanan, Borobudur, and Ratu Boko. Yet, the temple would only become a scenery or art spectacle if there were no somebody who tell the history of the temple, philosophy nor local wisdom values, order of human life, animal, plant, even heavenly creature that been shown through bas-relief surrounding the wall of the temple and mean of each shape of temple structure. Here is the responsibility of tour guide who have crucial roles in giving explanation to the tourist. Because of that, the management needs to cooperate with The Indonesian Tourist Guide Association so that the tourist would not find any difficulty to receiving explanation about the history of Prambanan. In attempt to find out tour guide roles in Prambanan area and partnership working between The Indonesian Tourist Guide Association and PT. Taman Wisata Candi Prambanan, Borobudur, and Ratu Boko, also find out the performance of tour guide that affect to services in Taman Wisata Candi Prambanan. So, researcher did some observation and interview with foreign tourist who used tour guide service. The valuation of tour guide performance uses criteria of ideal guide indicator that been described in some question about: a). language ability, b). knowledge of history, architecture, and local wisdom values, c). style of telling story, d). attitude and behavior, e). public speaking ability. The result of this research shows there is only one out of eight tour guide sample who has ideal criteria of telling story style, whereas the rest are not. It could be seen from the four respondents who gave bad valuation. Meanwhile, for attitude and behavior, nine respondents rated âgoodâ though the other two did not. There was one tour guide who have bad performance at the time of evaluation was held. It could be seen from the valuation of knowledge, style, attitudes, and public speaking. And then, the result of sixteen respondents would be drawn in star-shaped design. By meaning the clearer the shape, the better the value.